Lighting Design in Office Spaces: Illuminating the Path to Productivity and Well-being - Tanya Singh; Deepti Pande Rana* (International Journal of Environmental Planning and Development Architecture, 2024)
Lighting design in office spaces refers to the intentional planning and implementation of lighting solutions within a workplace environment to meet the functional, aesthetic, and psychological needs of occupants. This research paper delves into the intricate connection between lighting design, mood regulation, and productivity levels within office spaces. Through a comprehensive analysis of existing literature, it investigates how various aspects of lighting, including colour temperature, intensity, distribution, and dynamics, influence the psychological well-being and performance of employees. Additionally, the study explores the differential impacts of natural light versus artificial lighting systems on circadian rhythms, sleep quality, and overall workplace satisfaction. By considering individual preferences, task requirements, and environmental contexts, this research aims to provide insights into the optimization of lighting design for diverse office settings. Empirical research methods, such as surveys, observations, and experimental studies, are utilized to elucidate the nuanced effects of lighting on human behaviour and cognitive functions. Ultimately, this study aims to offer practical recommendations for architects, designers, and employers to create lighting environments that foster positive mood states and enhance productivity in office spaces, contributing to healthier, more engaging, and more effective work environments.
Keywords: Ambient lighting; Artificial light; Circadian rhythms; Colour temperature; Glare reduction; Illumination levels; Natural light; Task lighting; Visual comfort